Dorothy Cross - crossing - Long, Declan 19XX-; O'Brien, Edna 1930-2024; Hoare, Philip 1958-; Ní Ghríofa, Doireann 1981- (Dürer Editions, 2022)
Crossing by artist Dorothy Cross is a visual retrospective spanning over 35 years of her work as one of Ireland’s leading artists. The book includes a foreword by Edna O’Brien, essays by Philip Hoare, Doireann Ní Ghríofa and Declan Long. In hardback, and beautifully illustrated with over 125 photographs of the artist’s work, Crossing has an initial print run of 1,000 copies and is also available in a Limited Edition of 40 copies with a slipcase and an original signed print from the book. A Collectors Edition of 12 copies will also be available and will include a slipcase, an original signed print and a specially commissioned work by the artist entitled Mollusc cast in solid silver. Crossing looks at the various strands that connect and weave their way through her career, from her earliest works in the ‘90s to her latest exhibition ‘Damascus Rose’ at the Frith Street Gallery, in London 2022
First edition of 1000 copies
Keywords: Cross, Dorothy -- 1956-; Cross, Dorothy / 1956- / Exhibitions; Cross, Dorothy / 1956- / Catalogues raisonnés; Cross, Dorothy / 1956-; Bildband